1134. Novel T2Candida Panel Assay Compared With Blood Cultures for Detection of Candidemia in Transplant and Non-Transplant Patients. (26th November 2018) - Hussain, Noman; Chaudhry, Zohra; Rizvi, Hira; Abreu-Lanfranco, Odaliz; Ramesh, Mayur; Busto, Ramon Del; Osborn, Zachary; Alangaden, George
Abstract: Background: Blood culture (BC) the current "gold" standard for detection of candidemia has a sensitivity of ~50% and turnaround time (TAT) of 2–5 days. T2Candida Panel (T2) a magnetic resonance nano-diagnostic test done directly on blood samples detects C. albicans/C. tropicalis, C. krusei/C. glabrata, and C. parapsilosis . Clinical trials of T2 showed good sensitivity, specificity, NPV 99% and TAT of 3–5 hours. The performance of T2 in high-risk transplant (Tx) population is unknown. T2 was implemented at our institution in October 2015. We evaluated the performance characteristics of T2 and BC in our Tx and non-transplant (non-Tx) patient populations. Methods: This was an observational, retrospective, cross-sectional evaluation of patients with suspected candidemia that had T2 done from October 2015 to October 2017 at a multihospital healthcare system in Detroit, MI. Performance characteristics of the T2 and BC in Tx and non-Tx patients were compared. BC obtained within 7 days before or after the T2 test were included in the analysis. TAT, sensitivity, specificity, PPV and NPV were calculated using positive BC as the standard. Differences between groups were assessed using two sample proportions testing at α = 0.05. Results: A total of 1, 272 patients with suspected candidemia had T2 done: 1, 162 (91%) non-Tx and 110 (9%) Tx patients. Average TAT for T2 was 13 hours (5–41) vs. 34 hours (21–109) to initial positive BC result and 4 days (3–13) to species-specific BC result. In four non-Tx patients with negative T2, C. lusitaniae, C. dubliniensis, and C. kefyr were isolated in BC. Performance characteristics of T2 and BC in the two groups is shown (Table 1). Of the T2+/BC− cases ( n = 102), 9% had retinitis and 9% had invasive candidiasis. Conclusion: The rapid TAT, good sensitivity, and high NPV of T2 in Tx patients has clinical implications and can help support antifungal stewardship efforts in this population. The clinical significance of T2 positivity in the presence of negative BC needs further investigation. Disclosures: G. Alangaden, T2 Biosystems: Speaker's Bureau, Educational grant and Speaker honorarium.